2020
DOI: 10.1038/s41598-020-73960-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an antibody-dependent cellular cytotoxicity reporter assay for measuring anti-Middle East Respiratory Syndrome antibody bioactivity

Abstract: Middle East Respiratory Syndrome coronavirus (MERS-CoV) is a highly virulent pathogen that causes Middle East Respiratory Syndrome (MERS). Anti-MERS-CoV antibodies play an integral role in the prevention and treatment against MERS-CoV infections. Bioactivity is a key quality attribute of therapeutic antibodies, and high accuracy and precision are required. The major methods for evaluating the antiviral effect of antiviral antibodies include neutralization assays using live viruses or pseudoviruses are highly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Despite SARS-CoV-2, two coronavirus-induced epidemics have appeared over the past two decades, including SARS-CoV in 2003 and MERS-CoV in 2012. Researchers have observed an increase in ADCC activity induced by afucosylated anti-MERS antibodies than their fucosylated counterparts, which provides a novel perspective for evaluating the role of the modification of N -glycosylation of the Fc segment in improving ADCC activity ( 37 ). Moreover, mechanistic experiments demonstrated that during dengue infection, afucosylated IgG promotes FcγRIIIa signaling, and then enhances replication of the virus in monocytes ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite SARS-CoV-2, two coronavirus-induced epidemics have appeared over the past two decades, including SARS-CoV in 2003 and MERS-CoV in 2012. Researchers have observed an increase in ADCC activity induced by afucosylated anti-MERS antibodies than their fucosylated counterparts, which provides a novel perspective for evaluating the role of the modification of N -glycosylation of the Fc segment in improving ADCC activity ( 37 ). Moreover, mechanistic experiments demonstrated that during dengue infection, afucosylated IgG promotes FcγRIIIa signaling, and then enhances replication of the virus in monocytes ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear factor of activated T-cells (NFAT) signaling pathway is essential for Fcγ receptors (FcγRs) activation, which plays a critical role in ADCC and ADCP ( Aramburu et al, 1995 , Oh-hora and Rao, 2009 ); the NFAT-reporter systems are commonly used as surrogate ADCC or ADCP effectors. Human FcγRIIa (CD16a) or FcγRIIIa (CD32a)-expressing NFAT reporter cells are widely-used effector cells for ADCC or ADCP measurements for therapeutic monoclonal antibodies (mAbs) ( Cao et al, 2020 , Cheng et al, 2014 , Liu et al, 2021 , Parekh et al, 2012 ). In this study, we generated cells with stable expression of full-length SARS-CoV-2 spikes as target cells and developed NFAT-reporter cell-based assays for measurements of ADCC and ADCP activities of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…The ADCC effector cells Jurkat/NFAT‐luc/FcγRⅢa were developed as described previously 14 . Briefly, Jurkat T cells were first transfected by electroporation with plasmid pcDNA3.1, which expresses the human FcγRⅢa, and G418‐resistant cell clones were screened by fluorescence‐activated cell sorting for FcγRⅢa expression.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional ADCC assay that uses peripheral blood mononuclear cells or NK cells isolated from human blood as effector cells is not suitable for routine quantitative measurement of ADCC activity due to poor reproducibility and low sensitivity. Our laboratory has established several reporter gene‐based bioactivity determination methods, 10–13 including the ADCC assay for anti‐MERS antibodies, 14 and these methods have obvious advantages compared with traditional methods. For RABV, to date, only a few studies have demonstrated that anti‐RABV antibodies and lymphocytes from human peripheral blood could mediate the lysis of infected cells by ADCC 15,16 …”
Section: Introductionmentioning
confidence: 99%